What matters the adherence with BP 24-hr self-monitoring wearable device among hypertensive patients? A population-based survey. Issue 4 (5th June 2019) - Zhang, Yuting; Yang, Ningxi; Si, Guanglin; Zhang, Yupeng; Dong, Zhuangzhuang; Huang, Yuwei; Tan, Xiaodong
Abstract: Wearable mobile health (mHealth) technologies are a convenient and cost-effective community-based intervention to improve management of hypertension in resource-limited populations. This study was designed to evaluate user characteristics of blood pressure (BP) wearable technology among a community-based population in a rural area of China. During the period of April through July 2018, a self-monitoring intervention program for hypertension control was implemented in a remote area of central China. Participants completed a cross-sectional survey which included demographic characteristics, Technology Fluency, the Compliance of Hypertensive Patients' Scale, and the Health-related Quality of Life Survey. Participants were given a wearable BP-monitoring device which wirelessly uploaded data and monitored for 1 month. Participants ( n = 317) were 64.57 years ( SD = 11.68), 53.94% were male. During the 30-day monitoring, 52.68% of the sample uploaded BP wristband data daily were identified as "BP device users." No differences existed between device users and nonusers related to cardiovascular health measurements, technology fluency, and health-related quality of life. Device users were more likely to report a higher level of hypertension compliance. Individuals reporting a higher level of compliance in hypertension management are more likely to interact with a wearable BP-monitoring device than persons with lower levels of compliance. Further evaluation of mobile health systems involving a wearable device as part of a hypertension management program is needed in a resource-limited community-based setting.